2002
DOI: 10.1002/1521-3919(20020601)11:5<462::aid-mats462>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ion Pair Formation on the Phase Behavior of Polyelectrolyte Solutions

Abstract: In this paper we calculate the phase diagrams of polyelectrolyte solutions taking into account the possibility of ion pair formation between counterions and ions on polymer chains with their subsequent aggregation in multiplets. Multiplets play a role of reversible physical crosslinks between different polymer chains. Furthermore, we assume that the dielectric constant, and hence the binding energy of ion pairs and multiplets, depends on the volume fraction of polymer in the solution. We have shown that ion pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
52
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 12 publications
7
52
0
Order By: Relevance
“…This effect has been described in several theoretical works [17][18][19]21,[25][26][27] and has also been shown in Monte-Carlo simulations 20 . However, to the best of our knowledge theoretical models correctly predicting critical parameters of such a purely electrostatics driven phase transition are still missing.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…This effect has been described in several theoretical works [17][18][19]21,[25][26][27] and has also been shown in Monte-Carlo simulations 20 . However, to the best of our knowledge theoretical models correctly predicting critical parameters of such a purely electrostatics driven phase transition are still missing.…”
Section: Introductionsupporting
confidence: 61%
“…In work 27 the contribution of the correlation attraction was described at the level of mean-spherical approximation (MSA) that allowed to obtain a good agreement with simulation results for critical temperature but underestimated the critical monomer concentration. Secondly, most theoretical approaches [17][18][19]21,25,26 ignore the effects of the monomer concentration fluctuations in the regime of semi-dilute polymer solution. However, these effects, as was already mentioned above, should be important for solutions of polyelectrolytes as well as for neutral polymers 1,12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the theories [1][2][3][4][5][6][7][8][9][10][11][12][13][14] of coexistence of polyelectrolyte phases, formulated so far, with varying levels of approximations, have the common key assumption that each polyelectrolyte chain maintains the same constant effective charge for all coexisting phases at all allowed ranges of temperature, polyelectrolyte concentration, and salt concentration. This assumption cannot be correct in view of the large body of literature, based on theoretical arguments, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] computer simulations, [31][32][33][34][35][36][37][38] and experiments, [39][40][41][42][43][44][45][46][47]…”
Section: Introductionmentioning
confidence: 99%
“…non-fixed backbone charge have been considered in the context of non-geling, weakly charged polymers 18 , as well as for charged chemical gels. Many of the properties described in those works are likely to carry over to the case of weakly charged thermoreversible gels 22 . We have also previously reported that addition of doubly ionizing monomers to the polymer backbone (of LCST type) induces features in the swelling and phase separation behavior that might quantitatively different from those of equivalent systems with double amount of singly ionizable monomers 11 .…”
Section: Discussionmentioning
confidence: 96%